Branded Content Analysis (BCA): Four Models and Approaches - Wijaya, Bambang Sukma (Jobmark: Journal of Branding and Marketing Communication, 2021)
Branded content is any content that contains brand elements, either expressly or impliedly. Branded Content Analysis (BCA) analyzes branded content and finds explicit and implied meanings related to brand communication strategy. There are four BCA models and approaches. First, Directional BCA, which is the BCA method that uses a specific theoretical lens or concept to read the textual meaning of content, both verbal, visual, aural, audiovisual, textural, and nasal. Thus text coding is based on fundamental concepts that exist in theory. Second, Natural BCA, namely the BCA approach, does not use concepts or theories to read the textual meaning of content but naturally finds meaningful patterns that refer to key themes that stand out in the text. Third, Conditional BCA, namely the BCA method, depends on the tendency of issues framing in the text based on the dominant keywords. Fourth, Instrumental BCA, namely the BCA method, focuses on how content influences audiences through fundamental modes facilitated by the media, both textually, technically, and kinetically.